Critical and reflexive analysis of the syllabus of the subject of Obstetric and Gynecological Nursing of the discipline of Nursing - Lareisy Borges-Damas; Ana Gladys Peñalver-Sinclay; Rolando Sánchez-Machado; Edwar Parra-Linares (Revista Electrónica Dr. Zoilo E. Marinello Vidaurreta, 2018)
Background: the syllabus of the subject is the document that presents the systematic and hierarchical description of the general objectives to be achieved and of the essential contents to be assimilated, by providing the future graduate with the knowledge for an excellent professional performance. Objective: to carry out a critical, reflexive and evaluative analysis of the syllabus of the subject of Obstetric and Gynecological Nursing in the major of Nursing, taking into account the regulations currently in force for the methodological teaching work. Methods: a systematic review of the content of documents was carried out, where regulations and resolutions were considered, as well as original and review articles. The search began with the general syllabus of the discipline of Nursing and the syllabus of the subject of Obstetric and Gynecological Nursing, the current regulation for the methodological teaching work, the resolution 210/07 and the professional profile of the Licentiate in Nursing. Results: the study guides, in a methodological way, how to favor the formulation of comprehensive objectives from a developing perspective, and proposes conceptions that reflect the need of reassessing the contents (skill and knowledge systems), as well as the methodological guidelines for each topic, so that the general skills for the excellent exercise of the profession be determined. Conclusions: the critical analysis of the subject of Obstetric and Gynecological Nursing was carried out.